2022
DOI: 10.3390/vaccines10081185
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Parental Knowledge and Beliefs on HPV Vaccine Hesitancy in Kenya—Findings and Implications

Abstract: Cervical cancer can be prevented by human papillomavirus (HPV) vaccination. However, parents can have concerns about vaccinating their daughters. Consequently, there is a need to identify prevalence and risk factors for HPV vaccine hesitancy among parents in Kenya. A descriptive cross-sectional study was conducted among parents with children aged 9–14 years attending a leading referral hospital in Kenya. Data on sociodemographic traits, HPV knowledge, beliefs and vaccine hesitancy were collected. Out of 195 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 76 publications
3
9
0
Order By: Relevance
“…Our integrated health behaviour model offers a novel way of visualizing how these factors are interrelated. We found that perceived sexual inactivity of adolescents (34,(39)(40)(41), insu cient knowledge about vaccination timing, safety and effectiveness (24,(41)(42)(43) and preference for 9vHPV vaccine in uenced parents' individual decision and were consistent with determinants of vaccine hesitancy identi ed from studies conducted in the United States, Kenya and Japan. Furthermore, systemic barriers such as supply shortage, inadequate communication and dissemination of information (40)(41)(42) also contributed to hesitancy.…”
Section: Discussionsupporting
confidence: 75%
“…Our integrated health behaviour model offers a novel way of visualizing how these factors are interrelated. We found that perceived sexual inactivity of adolescents (34,(39)(40)(41), insu cient knowledge about vaccination timing, safety and effectiveness (24,(41)(42)(43) and preference for 9vHPV vaccine in uenced parents' individual decision and were consistent with determinants of vaccine hesitancy identi ed from studies conducted in the United States, Kenya and Japan. Furthermore, systemic barriers such as supply shortage, inadequate communication and dissemination of information (40)(41)(42) also contributed to hesitancy.…”
Section: Discussionsupporting
confidence: 75%
“…In the US, the authors found that parental confidence in the COVID-19 vaccines was critical to increasing the number of children and adolescents vaccinated [69]. This is similar to other countries and other vaccines for children, including HPV vaccines [84,92,[99][100][101]. These findings indicate a key role of parents and caregivers in improving the acceptance and uptake of COVID-19 vaccines among children and adolescents.…”
Section: Plos Global Public Healthmentioning
confidence: 55%
“…Considering the problems most frequently described in recent international studies as the cause of non-vaccination [ 45 , 46 , 47 ], we note the lack of information and confusion regarding adverse effects, which can be solved through education. Recommendations for HPV vaccination coming from professional is also important [ 46 ].…”
Section: Discussionmentioning
confidence: 99%